BOOK REVIEWS (Bioethics, 1991)
Book Reviws in this Article Shaping Genes: Ethics, Law and Science Using Genetic Technology in Medicine and Agriculture, DarrylR.J. Macer. Christchurch, N.Z. Eubios Ethics Institute, 1990 Suicide and Euthanasia: Historical and Contemporary Themes (Philosophy and Medicine 35), Baruch A. Brody (ed.) Dordrecht and Boston: Kluwer Academic Publishers (1989) Who Lives? Who Dies? Ethical Criteria in Patient Selection by John Kilner. New Haven: Yale U.P., 1990 Beyond BabyM: Ethical Issues in New Reproductive Techniques edited by Dianne M. Bartels, Reinhard Priester, Dorothy E. Vawter and Arthur L. Caplan. Clifton, N.J: Humana Press, 1989 Surrogate Motherhood The Legal and Human Issues by Martha A. Field. Cambridge, Mass: Harvard Univ. Press Medico-Legal Aspects of Parenthood and Reproduction, by J.K. Mason. Aldershot, U.K: Dartmouth Pub. Co., 1990 Philosophical Ethics in Reproductive Medicine: Proceedings of the First International Conference on Philosophical Ethics in Reproductive Medicine, University of Leeds, 18-22 April, 1988. Ed. by David R. Bromham, Maureen E. Dalton and Jennifer Jackson. Manchester: Manchester University Press, 1990